Role of the nitric oxide-soluble guanylyl cyclase pathway in cognitive deficits in streptozotocin-induced diabetic rats - ARICIOĞLU, FEYZA (TAYLOR & FRANCIS LTD, 2019)
OBJECTIVES: The impairment of cognitive functions in diabetes mellitus (DM) is well known. Nitric oxide (NO)-guanyly cyclase (GC)-cyclic guanosine monophosphate (cGMP) pathway is an important role in cognitive functions, and, consequently, phosphodiesterase-5 (PDE-5) inhibitors as well as NO-GC activators are of considerable interest in the treatment of cognitive deficits. Therefore, we aimed to investigate the effects of YC-1 (3-5-hydroxymethyl-2-furyl)-1-benzyl-indazole), an NO-GC activator, and zaprinast, a PDE-5 inhibitor, on cognitive dysfunction in streptozotocin (STZ)-induced diabetic rats. METHODS: Male Wistar rats were divided into five groups (nine rats in each): Control, Vehicle (DMSO), Diabetic (50 mg/kg/i.p. streptozotocin), Diabetic-YC-1 (1 mg/kg/day/i.p., for 4 weeks), and Diabetic-Zaprinast (10 mg/kg/day/i.p., for 4 weeks) group. The Morris water maze, passive avoidance, locomotor activity, and foot shock sensitivity tests were applied to assess the effect of YC-1 and zaprinast on learning and memory. To explore the mechanisms of YC-1 and zaprinast on learning and memory performance, protein expressions of brain-derived neurotrophic factor (BDNF) in hippocampus were examined immunohistochemically. RESULTS: Thirty days after the induction of DM, rats exhibited severe learning and memory dysfunctions associated with decreased BDNF expression. Both chronic YC-1 and zaprinast treatment improved cognitive performance and hippocampal BDNF expression in diabetic rats. In the locomotor activity and foot shock sensitivity test, no significant differences were observed between the groups. Furthermore, hyperglycaemia did not affect cognition enhancement effects of YC-1 or zaprinast in diabetic rats. CONCLUSIONS: Our findings highlight the beneficial effects of nitric oxide-guanylyl cyclase activators and PDE-5 inhibitors to improve cognitive function in diabetes.
Keywords: Diabetes mellitus; YC-1; zaprinast; passive avoidance; Morris water maze; dementia; DEPENDENT PROTEIN-KINASE; LONG-TERM POTENTIATION; MESSENGER-RNA EXPRESSION; PHOSPHODIESTERASE-5 INHIBITOR; MOUSE MODEL; CGMP LEVELS; IN-VIVO; MEMORY; SILDENAFIL; BRAIN